HUBUNGAN PEMBERIAN KUNYIT ASAM JAWA DENGAN KEJADIAN KEPUTIHAN PADA REMAJA PUTRI - Nurmaliza Nurmaliza; Rini Hariani Ratih; Yusmaharani Yusmaharani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
According to the World Health Organization (WHO) (2013) there are 75% of women who have experienced vaginal discharge once in their lifetime and 45% of them can experience vaginal discharge twice or more. One of the drinks that can reduce vaginal discharge is tamarind turmeric drink because it contains curcuminoid compounds, ethanol and chlorine, which contains antifungals and can kill bacteria, which can cause vaginal discharge. The purpose of this study was to determine the relationship between the administration of tamarind turmeric and the incidence of vaginal discharge in adolescent girls in class X at SMAN 7 Pekanbaru in 2022. This type of research was quantitative with a cross sectional design. The time of the study was from Mey - June 2022, the population in the study was class X teenage girls who experienced vaginal discharge as many as 30 respondents and a sample of 28 people, with Stratified Random Sampling sampling technique. The analysis used was univariate and bivariate. Based on the results of the chi square test, the p-value < (0.000 < 0.05), then Ho was rejected and Ha was accepted, meaning that there was a relationship between the administration of tamarind turmeric and the incidence of vaginal discharge at SMAN 7 Pekanbaru in 2022. It is hoped that the research site will provide references, especially regarding vaginal discharge, in order to increase the insight of young women so that they avoid the symptoms of vaginal discharge.Keywords: Tamarind turmeric, Leucorrhoea, Young women.